Exosomes: a promising avenue for cancer diagnosis beyond treatment - Wang, Zhu; Wang, Qianqian; Qin, Feng; Chen, Jie (Frontiers in Cell and Developmental Biology, 2024)
Exosomes, extracellular vesicles secreted by cells, have garnered significant attention in recent years for their remarkable therapeutic potential. These nanoscale carriers can be harnessed for the targeted delivery of therapeutic agents, such as pharmaceuticals, proteins, and nucleic acids, across biological barriers. This versatile attribute of exosomes is a promising modality for precision medicine applications, notably in the realm of cancer therapy. However, despite their substantial therapeutic potential, exosomes still confront challenges tied to standardization and scalability that impede their practice in clinical applications. Moreover, heterogeneity in isolation methodologies and limited cargo loading mechanisms pose obstacles to ensuring consistent outcomes, thereby constraining their therapeutic utility. In contrast, exosomes exhibit a distinct advantage in cancer diagnosis, as they harbor specific signatures reflective of the tumor's genetic and proteomic profile. This characteristic endows them with the potential to serve as valuable liquid biopsies for non-invasive and real-time monitoring, making possible early cancer detection for the development of personalized treatment strategies. In this review, we provide an extensive evaluation of the advancements in exosome research, critically examining their advantages and limitations in the context of cancer therapy and early diagnosis. Furthermore, we present a curated overview of the most recent technological innovations utilizing exosomes, with a focus on enhancing the efficacy of early cancer detection.